Scaling of Droplet Breakup in High-Pressure Homogenizer Orifices. Part II: Visualization of the Turbulent Droplet Breakup - Benedikt Mutsch; Felix Johannes Preiss; Teresa Dagenbach; Heike Petra Karbstein; Christian J. Kähler (ChemEngineering, 2021)
Emulsion formation is of great interest in the chemical and food industry and droplet breakup is the key process. Droplet breakup in a quiet or laminar flow is well understood, however, actual in-dustrial processes are always in the turbulent flow regime, leading to more complex droplet breakup phenomena. Since high resolution optical measurements on microscopic scales are extremely dif-ficult to perform, many aspects of the turbulent droplet breakup are physically unclear. To over-come this problem, scaled experimental setups (with scaling factors of 5 and 50) are used in con-junction with an original scale setup for reference. In addition to the geometric scaling, other non-dimensional numbers such as the Reynolds number, the viscosity ratio and the density ratio were kept constant. The scaling allows observation of the phenomena on macroscopic scales, whereby the objective is to show that the scaling approach makes it possible to directly transfer the findings from the macro- to the micro-/original scale. In this paper, which follows Part I where the flow fields were compared and found to be similar, it is shown by breakup visualizations that the turbulent droplet breakup process is similar on all scales. This makes it possible to transfer the results of detailed parameter variations investigated on the macro scale to the micro scale. The evaluation and analysis of the results imply that the droplet breakup is triggered and strongly influenced by the intensity and scales of the turbulent flow motion.